Two-dimensional fast lagrangian vortex method for simulating flows around a moving boundary / Duong Viet Dung, Lavi Rizki Zuhal and Hari Muhammad - Dung, Duong Viet; Zuhal, Lavi Rizki; Muhammad, Hari (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2015)
This paper presents the development of an accelerated two-dimensional core spreading vortex method for simulating flows over a moving boundary. The complex geometry is treated as tracking particles, which are introduced within the extended fluid domain. The boundary conditions are enforced by generating wall vortex blobs at each time step based on representation of Nascent vortex elements. The viscous effect is modeled by core spreading method, with splitting and merging spatial adaptation scheme. The velocity field is calculated by using Biot-Savart formulation. In order to accelerate computation, the fast multipole method is also employed. The solver is validated by performing the simulations of flow around an impulsively moving cylinder at Reynolds number 550, and flow over a forced-oscillating flat plate at Reynolds number 10000. The results are found to be in good agreement with those reported in literatures. Journal of Mechanical Engineering Vol. 12, No. 1, 31-46, 2015